Where does Bulgaria stand? - Davidkov, Tsvetan (Papeles del Este, 2004)
The article presents the results of an empiric sociological survey entitled “Organizational Culture in Bulgaria – 2000 – 2002”, which was carried out following the methodology of Geert Hofstede (Hofstede, 1980). It studies the procedure of calculating the indices of power distance, uncertainty avoidance, individualism – collectivism and masculinity – femininity. On the basis of the abovementioned Bulgaria is compared in score rate tables with other (mainly European) countries. An attempt is made to formulate the characteristics of Bulgarian national culture as well as organizational culture in Bulgaria.